RANK/RANKL/OPG Signaling in the Brain: A Systematic Review of the Literature - Glasnović, Anton; O'Mara, Niall; Kovačić, Nataša; Grčević, Danka; Gajović, Srećko (Frontiers in Neurology, 2020)
Together with its dominant immunological and bone remodeling involvement, RRO axis, comprising of receptor activator of nuclear factor-κB (RANK), RANK ligand (RANKL), and osteoprotegerin (OPG) signaling, is as well implicated in CNS functioning and corresponding pathologies. The CNS aspects of RANKL/RANK/OPG (RRO) axis were systematically reviewed. With search 10 databases, and 7 additional resources from first article publication to July 2019., resulted in total 2222 hits, from which 33 relevant papers were selected. The elements of RRO axis in CNS include cells involved in neuroinflammation, predominantly in microglia, but as well in resident macrophages and inflammatory cells migrating across the blood-brain barrier. The expression in neurons and oligodendrocytes is mainly confined to processed of differentiation and cell death. RRO axis tunes the neuroinflammatory response, depending on the molecular, cellular and pathological context. RANK/RANKL signaling is neuroprotective in TLR-mediated inflammation, while OPG seems detrimental in stroke, but beneficial in multiple sclerosis. The levels of RRO axis elements can serve as biomarkers in the blood and cerebrospinal fluid. They can serve as neuroprotectant after brain damage even being implicated in body weight- and thermo-regulation. As derivatives of RRO axis already serve as therapeutic agents in bone remodeling, it would be exciting to see if these or new RRO-based pharmaceuticals would appear effective in CNS therapies.